Reading Al-Ibānah: Habib Salim bin Jindan’s Eclectic Responses to Islamic Ritual Debates in Early 20ᵗʰ Century Indonesia - Abror, Muhamad; Lufaefi; Islam, M. Adib Misbachul; Yasrul Huda; Muhammad Nuril Fauzan (Jurnal Lektur Keagamaan, 2025)
This study examines the construction of the concept of bid‘ah in the manuscript al-Ibānah fī Tārīkh al-Sunnah by Habib Salim bin Jindan as a response to traditionalist and reformist debates in early twentieth-century Indonesia. Its aim is to trace how Habib Salim’s eclectic perspective emerged through the interplay of hadith authority, Ba‘Alawi genealogical tradition, and engagement with Islamic reformist discourse. The primary data are drawn from al-Ibānah, particularly sections addressing the definition of bid‘ah, additions to prescribed religious practices, and ritual examples such as bodily movements during dhikr, ḥaul commemorations, and non-canonical prayers (Raghā’ib and ʿĀshūrā’). The study employs philological methods to examine the structure and textual presentation of the manuscript, alongside a socio-intellectual historical approach to contextualize al-Ibānah within the development of Indonesian Islamic thought. The analysis reveals that the manuscript advances a framework of bid‘ah that does not fully align with either traditionalist or reformist paradigms. Habib Salim challenges claims from both camps through more flexible classifications and hadith-based argumentation. The findings revise prevailing understandings of Hadrami scholars, who have often been positioned dichotomously in historical narratives. The article’s contribution lies in its reading of religious manuscripts as sources of discourse, its explanation of the intellectual authority of Hadrami sayyids, and its reframing of the dynamics of religious critique within the intellectual history of Indonesian Islam.